2020
DOI: 10.1042/ebc20200013
|View full text |Cite|
|
Sign up to set email alerts
|

Base excision repair and its implications to cancer therapy

Abstract: Abstract Base excision repair (BER) has evolved to preserve the integrity of DNA following cellular oxidative stress and in response to exogenous insults. The pathway is a coordinated, sequential process involving 30 proteins or more in which single strand breaks are generated as intermediates during the repair process. While deficiencies in BER activity can lead to high mutation rates and tumorigenesis, cancer cells often rely on increased BER activity to tolera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
50
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(50 citation statements)
references
References 108 publications
0
50
0
Order By: Relevance
“…Upregulation or down regulation of the BER pathway can lead to resistance or sensitivity, respectively, to these agents. Several inhibitors of the BER pathway are also in development ( Grundy et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Upregulation or down regulation of the BER pathway can lead to resistance or sensitivity, respectively, to these agents. Several inhibitors of the BER pathway are also in development ( Grundy et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Measuring just DNA strand breaks with the conventional comet assay gives limited information on the total and type of DNA damage induced, as the direct effect of some damaging agents will be the generation of modified bases (e.g., oxidative DNA damage), but also sites of base loss (apurinic/apyrimidinic or AP sites) that are alkali labile and therefore appear as breaks under alkaline comet assay conditions (pH > 13). AP sites will also be generated as intermediates during base excision repair of DNA base damage [ 8 ]. Moreover, it is generally accepted that, by performing the comet assay using neutral pH conditions (pH = 8), only DNA double strand breaks (DSBs) are detected, and there is plentiful published evidence to support this.…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that APE1 redox inhibitors in combination with cisplatin inhibit proliferation of bladder cancer cells more efficiently than cisplatin alone (Fishel et al, 2019). Currently, specific inhibitors against BER proteins such as Polβ, PNKP, FEN1, Ligase IIIα, and PARP1/PARG have been developed either to sensitize several cancers or to form synthetic lethal partnerships with common cancer mutations (reviewed in Grundy and Parsons, 2020).…”
Section: Aberrant Repair Of Interstrand Dna Cross-linksmentioning
confidence: 99%